Lifting the biofilm lid on the antibacterial and antibiofilm effects of sodium hypochlorite against Staphylococcus aureus in atopic dermatitis. (August 2017) - Harris, V.; Smith, S.D.
Abstract : Linked Article:Eriksson et al . Br J Dermatol 2017;177 :513–521 .